A novel alphanumeric classification system for ankle fractures: clinical applications and evaluation - Cemil Aktan; Ozkan Kose (Journal of Orthopaedic Surgery and Research)
Abstract Purpose The purpose of this study was to introduce and evaluate the Descriptive Ankle Fracture Classification (DAFC) system, a novel alphanumeric method for categorizing ankle fractures and fracture dislocations, and to assess its reliability and prognostic value compared to traditional classification systems (AO/OTA, Weber, and Lauge-Hansen). Materials and methods A retrospective review was conducted on 90 patients who underwent surgical treatment for ankle fractures. Four observers of varying experience levels classified the fractures using the DAFC, AO/OTA, Weber, and Lauge-Hansen classification systems. Interobserver and intraobserver reliability were evaluated using Fleiss’ Kappa coefficient. Functional outcomes were assessed with the American Orthopaedic Foot & Ankle Society (AOFAS) and Olerud Molander Ankle Score (OMAS) systems, and comparisons were made across classification systems to determine prognostic value. Results The DAFC system demonstrated superior interobserver reliability, particularly for medial malleolus fractures (Kappa = 0.935–0.954) and syndesmotic injuries (Kappa = 0.873–0.891), compared to the other systems. Intraobserver reliability was consistently high across all categories in the DAFC system, with Kappa values ranging from 0.967 to 1.000. Functional outcomes revealed significant associations with the DAFC classification: patients with complete dislocation (D2) had significantly lower AOFAS and OMAS scores than those without dislocation (D0) (P = 0.011), and those with larger posterior malleolus fractures (P2) had poorer OMAS scores (P = 0.014). No statistically significant differences in AOFAS or OMAS scores were observed across AO/OTA, Weber, or Lauge-Hansen classifications. Conclusions The DAFC system offers a reliable and comprehensive framework for ankle fracture classification, with the added benefit of prognostic insights, particularly regarding dislocation and posterior malleolus involvement. Its high interobserver and intraobserver reliability, even among observers with varying experience, suggests that the DAFC system is valuable for clinical use. Future research should focus on validating these findings in larger cohorts and assessing the DAFC system’s impact on long-term patient outcomes. Level of evidence Level IV, Retrospective cohort.